Association between different infection profiles and one-year outcomes in ANCA-associated vasculitis: a retrospective study with monthly infection screening. Issue 2 (21st October 2022) - Xu, Tingting; Chen, Zijin; Jiang, Mengdi; Ma, Hunkun; Jin, Kexin; Wang, Zhiyu; Wang, Chongjian; Xu, Jing; Zhang, Wen
Abstract : Objectives: This study aimed to explore clinical features of early infection in patients with antineutrophil cytoplasmic antibody-associated vasculitis (AAV) and to identify the association between the infection profile of patients with AAV during the first 3 months and 1-year survival. Methods: A total of 415 newly diagnosed patients with AAV in the Department of Nephrology at Shanghai Ruijin Hospital from 2000 to 2018 were included. Four Cox regression models were used to analyse the association based on demographics, comorbidities, laboratory baseline index and therapy parameter. Infection screening was carried out monthly during the first 3 months after diagnosis. Results: In all, 377 episodes of infection were identified among 220 patients during the first 3 months. The overall survival after 1 year was 73.0%. Respiratory infection (210 episodes/164 persons) accounted for more than half of infections. Infection was independently associated with 1-year mortality (adjusted HR 2.32, 95% CI 1.27 to 4.23, p=0.006) after adjustment. Respiratory infection (adjusted HR 4.36, 95% CI 2.86 to 8.06, p<0.001), Gram-negative bacterial infection (adjusted HR 1.71, 95% CI 1.01 to 2.91, p=0.047) and fungal infection (adjusted HR 1.77, 95% CI 1.07 to 2.94, p=0.026) was identified as a risk factor for 1-year mortality. Trimethoprim-sulfamethoxazole (TMP-SMX) prophylaxis (adjusted HR 0.55, 95% CI 0.31 to 0.97, p=0.040) was protective for 1-year mortality. Conclusions: Infections, particularly respiratory infections, are a common and important class of complication in patients with AAV and are associated with early mortality. TMP-SMX prophylaxis might be necessary to improve short-term outcome. More consideration of infectious risk and regular infection screening should be given.